Mercenaries and paid men : the mercenary identity in the Middle Ages : proceedings of a conference held at University of Wales, Swansea, 7th-9th July 2005 - France, John (History of warfare ;, 2008)
Mercenaries have always had a poor press. Theirs is one of the world's oldest professions, but the very word has profoundly negative connotations of infidelity and ruthlessness. But if they were like this, were they so different from soldiers?